Alveolar type 2 cells marker gene SFTPC inhibits epithelial-to-mesenchymal transition by upregulating SOX7 and suppressing WNT/β-catenin pathway in non-small cell lung cancer - Zhang, Qiongyin; An, Ning; Liu, Yang; Zhu, Ying; Pan, Wuliang; Gu, Peiling; Zhao, Jinzhu; Pu, Qiang; Zhu, Wen (Frontiers in Oncology, 2024)
IntroductionSurfactant Protein C gene (SFTPC) is a marker gene of alveolar type 2 cells (AT2), which are the key structures of alveoli. Mutations or deletions in SFTPC cause idiopathic pulmonary fibrosis (IPF). Importantly, IPF is an independent risk factor for non-small cell lung cancer (NSCLC). It suggests that abnormal expression of SFTPC may be relevant to development of NSCLC. However, the function and mechanism of SFTPC in NSCLC are still poor understood until now.MethodsThe expression of SFTPC and the relationship between SFTPC and prognosis of NSCLC were analyzed in TCGA database and our collected clinical NSCLC tissues. Subsequently, the function and mechanism of SFTPC in NSCLC were explored by RNA-sequence, qRT-PCR, Western blot, Immunohistochemical, Wound-healing, Millicell, Transwell assays and mouse tumor xenograft model.ResultsSFTPC was dramatically downregulated in NSCLC tissues from TCGA database and 40 out of 46 collected clinical LUAD tissues compared with adjacent non-tumor tissues. Low expression of SFTPC was associated with poor prognosis of LUAD by TCGA database. Importantly, we confirmed that overexpression of SFTPC significantly inhibited Epithelial-to-Mesenchymal Transition (EMT) process of NSCLC cells by upregulating SOX7 and then inactivating WNT/β-catenin pathway in vitro and in vivo. Particularly, we discovered that low expression of SFTPC was associated with EMT process and low expression of SOX7 in NSCLC tissues.ConclusionOur study revealed a novel mechanism of SFTPC in NSCLC development. Meanwhile, it also might provide a new clue for exploring the molecular mechanism about NSCLC development in patients with IPF in the future.